Using a Medication Plan as a Quality Indicator: Feasibility and Satisfaction Results from an Observational Study - K. Blondon; C. Skalafouris; M. Louis Simonet; V. Piguet (Journal of Family Medicine, 2019)
Background Medication adherence remains a challenge for patient management. Changes in the drug regimen after a hospital stay can lead to confusion or misunderstandings. We implemented a structured patient-centered interview during which a computer-generated individualized medication plan was discussed and provided to patients at discharge. Objective To explore whether a medication plan can be a quality indicator, in terms of its content (quality) and its implementation in the resident’s workflow (feasibility). Methods An observational mixed method study with interviews of 174 patients from general internal medicine wards at 1 week and 1 month after discharge, and of 91 physicians at baseline. We report the quality of the medication plan in terms of content and state of completion. We describe feasibility for residents to complete this plan, as well as patient and resident satisfaction with the plan. Results 83% of participants received a medication plan. Physicians verified renal function (83%) to adapt doses but did not regularly assess for medication interactions (43%). Incomplete plans (61%), were due to blanks when physicians considered the information irrelevant for their patients. Error rate was <3%. Patients reported low use of their plan after discharge (64% found it useful after 1 week, whereas only 37% used it when taking their medication 1 week after discharge). Conclusion Although the plans were considered useful by both patients and physicians, their implementation could have been optimized by considering the overall process (creation to patient use). Mobile apps could help fill gaps in supporting patients for medication adherence.
Keywords: Medication Plan